Oral manifestations in hospital-admitted COVID-19 patients: a case control study - Alhamed, Sana; Aljohani, Suad (Frontiers in Oral Health, 2023)
The oral cavity can present early manifestations of several systemic diseases. Since the emergence of the COVID-19 pandemic, there have been many published studies reporting the direct effect of the virus on orofacial structures. In the present study, oral signs and symptoms of 22 hospital-admitted COVID-19 patients were examined and compared to a matching control group. Loss of taste and smell was the most prevalent symptom (65%), followed by oral dryness (45%) and halitosis (30%). The most common oral lesions were candidal infections (68%). Other less common manifestations were oral ulcerations (36%) followed by the appearance of white patches (27.3%). There was a statistically significant association between candidal infection and age in the study group, where the p-value was 0.008. In the present study, 80% of those who had candida infections were aged 60 years or above. There was no significant association with comorbidities such as diabetes mellitus and hypertension.